M-Sign in Middle Cerebral Artery Doppler Waveforms: A Sign of Fetal Vasoconstriction Before and After Open Fetal Spina Bifida Repair - Vonzun, Ladina; Gonser, Markus; Moehrlen, Ueli; Mazzone, Luca; Meuli, Martin; Kandler, Lukas; Wille, David; Kraehenmann, Franziska; Zimmermann, Roland; Ochsenbein-Kölble, Nicole (Ultraschall in der Medizin - European Journal of Ultrasound, 2022)
Background Increased pulse wave reflection in the fetal arterial system, illustrated by a second systolic peak (M-sign) in middle cerebral artery (MCA) Doppler waveforms, allows interpretation of fetal systemic vasoconstriction. Little is known about fetal vascular regulation during fetal spina bifida (fSB) repair. Therefore, the aim of this study was to analyze MCA-Doppler waveform changes before, during, and after fSB repair. Patients and Methods 31 pregnant women who underwent fSB repair were included. Fetal MCA-Doppler waveforms were prospectively analyzed before, during and after fSB repair, and categorized as follows: normal systolic downslope, systolic shoulder, second systolic peak (M-sign), and concave systolic downslope. These MCA waveforms were related to maternal and fetal characteristics, to anesthetic medication, and to umbilical artery (UA) waveforms. Results Before fSB repair, all fetuses repeatedly presented M-signs. After initiation of desflurane for general anesthesia, systolic shoulder and the M-sign vanished in 24/31 (78%) fetuses and 19/31 (61%) showed transient UA ARED flow. A significant association between these two Doppler findings was found (p=0.007). After fSB repair, signs of increased pulse wave reflection reappeared but resolved over time (23 days ± 20, SD) in all fetuses. Conclusion Both fSB and intrauterine repair influence fetal vascular regulation. This phenomenon can be illustrated by MCA-Doppler waveforms. While anesthetic agents transiently eliminated M-signs and often provoked a UA ARED flow, fSB repair finally led to normalization of MCA-Doppler waveforms indicating return to normal fetal vascular regulation.
Keywords: fetal surgery; MCA-Doppler; second systolic peak; M-sign; myelomeningocele repair